2020
DOI: 10.31234/osf.io/frbkj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Offspring Study of Racial and Ethnic Disparities in Alzheimer’s Disease: Objectives and Design

Abstract: The Offspring Study of Racial and Ethnic Disparities in Alzheimer’s Disease began in 2017 to identify biological and sociocultural mechanisms of disparities in cognitive function among middle-aged people with and without a parent with Alzheimer's Disease (AD). This article outlines the objectives and design of this prospective cohort study aimed at advancing the understanding of risk factors among middle aged offspring in order to clarify pathways to AD, and provides background on recruitment and retention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 128 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…We included participants from 2 community-based studies of cognitive aging and dementia that enrolled older and middle-aged adults, the Washington Heights–Inwood Columbia Aging Project (WHICAP) and the Offspring Study of Racial and Ethnic Disparities in Alzheimer Disease (Offspring). Full descriptions of study procedures have been reported previously . Briefly, WHICAP participants were residents of northern Manhattan, New York, 65 years and older, and fluent in English and/or Spanish and were recruited in 3 waves, beginning in 1992, 1999, and 2009.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included participants from 2 community-based studies of cognitive aging and dementia that enrolled older and middle-aged adults, the Washington Heights–Inwood Columbia Aging Project (WHICAP) and the Offspring Study of Racial and Ethnic Disparities in Alzheimer Disease (Offspring). Full descriptions of study procedures have been reported previously . Briefly, WHICAP participants were residents of northern Manhattan, New York, 65 years and older, and fluent in English and/or Spanish and were recruited in 3 waves, beginning in 1992, 1999, and 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Full descriptions of study procedures have been reported previously. 16 Briefly, WHICAP participants were residents of northern Manhattan, New York, 65 years and older, and fluent in English and/or Spanish and were recruited in 3 waves, beginning in 1992, 1999, and 2009. The current analysis included WHICAP participants recruited from the 2009 cohort who received scans with 3-T MRI beginning in 2011.…”
Section: Participantsmentioning
confidence: 99%
“…We selected participants from the Washington Heights-Inwood Columbia Aging Project (WHICAP) and Offspring cohorts, two community-based studies of cognitive aging and dementia in residents of northern Manhattan, New York. Full descriptions of study procedures have been published previously 15 . Briefly, WHICAP participants were recruited in three waves, beginning in 1992, 1999, and 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, WHICAP is an ongoing longitudinal study that includes Medicare-eligible older adults (≥65 yrs) recruited from the community surrounding Columbia University Irving Medical Center (recruitment waves: 1992, 1999, 2009). Their adult children were contacted for participation in the Offspring study 27 . Self-reported race/ethnicity follows the 2000 Census guidelines 28 , and was performed independently for parents and offspring (i.e., there is slight mismatching across generations).…”
Section: Methodsmentioning
confidence: 99%